Back-to-monomer recycling of polycondensation polymers: opportunities for chemicals and enzymes. Issue 2 (5th January 2022) - Thiyagarajan, Shanmugam; Maaskant-Reilink, Evelien; Ewing, Tom A.; Julsing, Mattijs K.; van Haveren, Jacco
Abstract : This review highlights the promising strategies developed to break down polycondensate polymers back to monomers using chemicals and enzymes. Our aim is to create a renewed awareness to valorize plastic waste into virgin plastics. Abstract : The use of plastics in a wide range of applications has grown substantially over recent decades, resulting in enormous growth in production volumes to meet demand. Though a wide range of biomass-derived chemicals and materials are available on the market, the production volumes of such renewable alternatives are currently not sufficient to replace their fossil-based analogues due to various factors, in particular cost-effectiveness. Hence, the majority of plastics are still industrially produced from fossil-based feedstocks. Moreover, various reports have clearly raised concern about the plastics that are not recycled at their end-of-life and instead end up in landfills or the oceans. To avoid further pollution of our planet, it is highly desirable to develop recycling processes that use plastic waste as feedstock. Chemical recycling processes could potentially offer a solution, since they afford monomers from which new polymers can be produced, with the same performance as virgin plastics. In this manuscript, the opportunities for using either chemical or biochemical ( i.e., enzymatic) approaches in the depolymerization of polycondensation polymers for recycling purposes are reviewed. Our aim is to highlight the strategies that have been developed so far to break down plastic waste into monomers, providing the first step in the development of chemical recycling processes for plastic waste, and to create a renewed awareness of the need to valorize plastic waste by efficiently transforming it into virgin plastics.